Ritual journeys in South Asia: constellations and contestations of mobility and space - Bergmann, Christoph; Schaflechner, Jürgen (Routledge, Taylor & Francis Group, 2020)
In fear of the past: the pilgrimage to Badrinath in perspective / Hans Jürgen David -- Journeying sovereignties: ritual travelling and networks of power in a West Himalayan kingdom / Lokesh Ohri -- Wandering god: how young Himalayans negotiate religion, caste identity and modernity / Karin M. Polit -- Places, rituals and past worlds: encounters on a pilgrimage in Tibet / Nike-Ann Schröder -- Ritual displacement as process of constructing and de-constructing boundaries in a Sufi pilgrimage of Pakistan / Michel Boivin -- To worship our 'boss' (the Buddha): youth religiosity in a popular pilgrimage site in Sri Lanka / Premakumara de Silva -- Vailankanni Mata and Anglo-Indian Catholics: rising postcolonial devotion and her unlikely pilgrim devotees / Robyn Andrews and Brent Howitt Otto -- Muslim-Marathi pilgrimage: the Sufi-shrine of Viśālgaḍh / Deepra Dandekar -- Approaches to pilgrimage: reading some post-independence pilgrimage accounts in modern South Asian languages / Hans Harder -- Afterword: on pilgrimage and plural paradigms / Simon Coleman.
Includes bibliographical references and index
Keywords: South Asia -- Religious life and customs; Electronic books; Aufsatzsammlung; Ritualisierung; Wallfahrt; Südasien